Collecting kinematic data on a ski/snowboard track with panning, tilting, and zooming cameras: Is there sufficient accuracy for a biomechanical analysis? - Klous, M.; Müller, E.; Schwameder, H. (Journal of Sports Sciences, 2010)
For biomechanical research in several sports (e.g. skiing and snowboarding), field experiments are essential because these activities are performed over a great distance and in conditions that could not be reproduced in a controlled laboratory environment. High technical standards in kinematic set-up are necessary to achieve the required accuracy for biomechanical analysis. The purpose of this study was to determine the accuracy of the kinematic data collected in a ski and snowboard field experiment. Eight tests generally used in laboratory settings were adapted to field conditions on a skiing slope to determine the error related to motion capture. The calculated photogrammetric errors in the x-, y-, and z-direction were 11 mm, 9 mm, and 13 mm, respectively. The maximum error caused by soft tissue artifacts was 39 mm. These results indicate that accuracy of kinematic data in the described field experiment was comparable to that found in literature for laboratory experiments. It may be concluded that accurate kinematic data collection for skiing and snowboarding can be performed in a field setting and that these results are accurate enough to serve as input data for further analyses.